중소기업의 ESG 평가지표 활용 방안: ESG 평가지표와 기업가치의 관계를 중심으로 - 박재현(Park Jae Hyun); 한향원(Han Hyang Won) (벤처창업연구, 2023)
Recently, concerns are growing over small and medium-sized companies holding out on debt as domestic loan interest rates have risen sharply due to the prolonged impact of COVID-19 and soaring raw material prices. In addition, loans from small and medium-sized enterprises, which are difficult in the business environment, are increasingly being rejected due to high loan interest rates and excessive submission documents and financial statements-oriented screening of loans by the financial sector. Therefore, since it is necessary to discuss ways to promote financing and investment by SMEs, this study intends to suggest ways to promote investment through the use of SMEs' ESG systems. The purpose of this study is to suggest that the use of ESG evaluation indicators used as non-financial indicators helps predict the corporate value of SMEs and the importance of SMEs actively participating in ESG information disclosure. This study suggests the necessity of introducing and practicing ESG by SMEs where financing is important, and aims to analyze as an empirical result that the use of non-financial indicators helps predict corporate value. As a result of the study, the ESG performance and corporate value of SMEs showed a positive (+) relationship. It can be seen that both the grades and corporate value of SMEs by ESG sector have a positive (+) influence relationship. The total ESG rating was confirmed to have a positive effect on corporate value, and it was confirmed that SMEs with higher ESG environment, social, and governance ratings were evaluated higher. According to the research results, it is suggested that SMEs also need to use ESG evaluation indicators, and in order to promote the growth of SMEs, it is suggested that research on ways to re-examine the corporate value of SMEs is necessary. Therefore, this study suggests that the use of ESG should be actively recommended and implemented as a way to establish a management strategy for SMEs, and that efforts to disclose ESG information can soon help SMEs solve information asymmetry. In addition, SMEs want to understand the investment mechanism that the introduction and practice of ESG can lead to the improvement of the value of SMEs and suggest the necessity of SME-type ESG policies in the future. 최근 COVID-19 장기화 영향과 원자재 가격 급등으로 국내 대출금리가 가파르게 오르면서 빚으로 버티는 중소기업에 대한 우려가 커지고 있다. 또한, 높은 대출금리와 금융권의 대출심사 시 과도한 제출서류와 재무제표 위주의 심사로 인해 경영 환경에 힘든 중소기업의 대출은 거절되는 경우도 증가하고 있다. 따라서 중소기업의 자금조달과 투자 활성화 방안에 대한 논의가 필요하기에 본 연구는 중소기업의 ESG 제도의 활용을 통한 투자증진방안을 확인하였다. 본 연구의 목적은 비재무적 지표로 활용되는 ESG 평가지표의 활용이 중소기업의 기업가치를 예측하는 데 도움이 되며, 중소기업이 ESG 정보공시에 적극적으로 참여해야 하는 중요성을 제시하는 것이다. 본 연구는 자금조달이 중요한 중소기업의 ESG 도입과 실천의 필요성을 제언하며, 비재무적 지표의 활용이 기업가치를 예측하는 데 도움이 된다는 것을 실증적인 결과로 제시하였다. 연구결과, 중소기업의 ESG 성과와 기업가치는 정(+)의 관계를 가졌다. 중소기업의 ESG 부문별 등급과 기업가치는 모두 정(+)의 영향 관계를 맺는 것으로 볼 수 있다. ESG 종합등급은 기업가치에 긍정적 영향을 미치는 것으로 확인되었고 뿐만 아니라 ESG 환경, 사회, 지배구조 등급이 높은 중소기업일수록 기업가치를 높게 평가받는다는 것을 확인할 수 있었다. 연구결과에 따르면, 중소기업에게도 ESG 평가지표의 활용이 필요함을 제시하고, 중소기업의 성장을 도모하기 위해서는 중소기업의 기업가치를 재조명하는 방안을 연구하는 것이 필요함을 제언한다. 따라서, 본 연구는 중소기업의 ESG 경영과 기업가치의 관계에 대한 이해를 통해 중소기업의 ESG 경영 전략 수립 방안이 필요하다는 점과 ESG 정보공시를 위한 노력이 곧 중소기업의 정보 비대칭성을 해결하는 데 도움이 될 수 있음을 시사한다.